2019
DOI: 10.4067/s0034-98872019000200145
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume as a prognostic factor for venous thromboembolic disease

Abstract: Background: Mean platelet volume (MPV) is a risk factor for cardiovascular and inflammatory diseases. Aim: To evaluate the association between high MPV and 90-day mortality after an episode of venous thromboembolism (VTE). Material and Methods: Retrospective cohort of 594 patients with a median age of 73 years (58% women) with a first episode VTE, included in an institutional Thromboembolic Disease registry between 2014 and 2015. MPV values were obtained from the automated blood cell count measured at the mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
10
1
1
Order By: Relevance
“…Other reports suggest that MPV is associated with VTE risk and survival in cancer patients. [35][36][37] In the present study, we observed the high level of RDW-SD, MPV, sE-selectin, sVCAM-1, PAI-1, MCP-1 and sCD14 in cancer patients, although we could not recognize the significance of these markers in CAT. However, an interesting marker was MDMP, because MPs could associate with CAT.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Other reports suggest that MPV is associated with VTE risk and survival in cancer patients. [35][36][37] In the present study, we observed the high level of RDW-SD, MPV, sE-selectin, sVCAM-1, PAI-1, MCP-1 and sCD14 in cancer patients, although we could not recognize the significance of these markers in CAT. However, an interesting marker was MDMP, because MPs could associate with CAT.…”
Section: Discussioncontrasting
confidence: 75%
“…Several biomarkers have been reported in terms of CAT predictions thus far. [34][35][36][37][38][39] Zöller et al 34 reported that RDW-SD is associated with long-term incidence of the first event of VTE among middle-aged subjects, although not necessarily cancer. Other reports suggest that MPV is associated with VTE risk and survival in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Другое исследование продемонстрировало, что MPV является ФР неспровоцированной венозной тромбоэмболии, а это позволяет предположить, что MPV и активность тромбоцитов являются ФР для развития не только артериальных, но и венозных тромбозов [23]. В недавнем ретро-спективном исследовании Díaz J, et al установлено, что высокий уровень MPV (>11,0 фл) является независимым ФР смерти пациентов с венозными тромбоэмболиями [24]. Kostrubiec M, et al также сообщили, что повышенные уровни MPV (>10,9 фл) являются независимыми предикторами ранней смертности пациентов с острой легочной эмболией в течение 7 и 30 дней: ОШ =2,0 (95% ДИ 1,3-3,0), p<0,001 и ОШ =1,7 (95% ДИ 1,2-2,5), p<0,01, соответственно.…”
Section: Mpv как независимый фактор риска (фр) для ссзunclassified
“…Enhanced platelet activation as determined by mean platelet volume (MPV) is seen in cancer patients, and may correlate with tumor stage [122,123]. Both MPV and increased soluble P-selectin levels correlate with VTE development in cancer patients [124][125][126]. Age does not predict VTE risk for all cancer types, suggesting that at least for some cancer types, tumor cells themselves increase platelet reactivity and VTE risk [127].…”
Section: Platelet Bioactive Lipids In Agingmentioning
confidence: 99%